Importance of Microvascular Invasion Risk and Tumor Size on Recurrence and Survival of Hepatocellular Carcinoma After Anatomical Resection and Non-anatomical Resection - Hu, Haoyu; Qi, Shuo; Zeng, Silue; Zhang, Peng; He, Linyun; Wen, Sai; Zeng, Ning; Yang, Jian; Zhang, Weiqi; Zhu, Wen; Xiang, Nan; Fang, Chihua (Frontiers in Oncology, 2021)
Purpose To establish a valid prediction model to prognose the occurrence of microvascular invasion(MVI), and to compare the efficacy of anatomic resection(AR) or nonanatomic resection(NAR) for hepatocellular carcinoma(HCC). Methods 228 patients with HCC who underwent surgical treatment were enrolled.Their hematological indicators, MRI imaging features and outcome data were acquired. Result In the multivariable analysis, alpha-fetoprotein >15 ng/mL, neutrophil to lymphocyte ratio > 3.8, corona enhancement, and peritumoral hypointensity on hepatobiliary phase were associated with MVI. According on these factors, the AUROC of the predictive model in the primary and validation cohorts was 0.884 (95% CI: 0.829, 0.938) and 0.899 (95% CI: 0.821, 0.967), respectively. Patients with high risk of MVI or those with low risk of MVI but tumor size>5cm in the AR group were associated with a lower rate of recurrence and death than patients in the NAR group; however, when patients are in the state of low-risk MVI with tumor size≦5cm, there is no difference in the rate of recurrence and death between AR and NAR. Conclusion Our predictive model for HCC with MVI is convenient and accurate. Patients with high-risk of MVI or low-risk of MVI but tumor size>5cm executing AR is of great necessity.